Identifikasi Interaksi Padat Campuran Parasetamol dan Ibuprofen dengan Metode Thermal - Noviza, Deni; Zaini, Erizal (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Solid-state interaction between parasetamol and ibuprofen was studied using thermal and spectroscopic techniques. Parasetamol-Ibuprofen binary mixtures were prepared by rotary ball mill grinding method. Differential scanning calorimetry was used to investigate the stoichiometry and thermal properties of the complex between parasetamol and ibuprofen. Powder X-ray diffraction were used to investigate the type of interaction between the two components. Two endothermic peaks in a binary mixture of paracetamol and ibuprofen was observed in DSC thermograph. X-ray powder diffractogram do not shows shift and formation of new peaks and the position of each peak is a super-imposition of each component without dominates. It can be concluded that the solid interaction between paracetamol and ibuprofen for grinding effect is the formation of mixed crystal system.